The Permeation of Ammonium through a Voltage-independent K+ Channel in the Plasma Membrane of Rye Roots - White, P.J.
Nitrogen is available to the plant in the form of NH+4 in the soil solution. Here it is shown that a voltageindependent K+ channel in the plasma membrane of rye (Secale cereale L.)roots is permeable to NH+4 . The channel was studied following its incorporation into planar 1-palmitoyl-2-oleoyl phosphatidyl ethanolamine bilayers. The unitary conductance of the channel was greater when assayed in the presence of 100 mM NH4Cl than 100 mM KCl. However, the probability of finding the channel open (Po)was lower in the presence of 100 mM NH4Cl (Po40.63)than in 100 mM KCl (Po40.8), suggesting that Po can be regulated by the (permeant)ions present in solution. When assayed in equimolar concentrations of NH4Cl (cis)and KCl (trans), the zerocurrent (reversal)potential for the channel (Erev)exhibited a complex concentration dependence. At low cation concentrations, the apparent permeability of NH+4 relative to K+ (PNH4/PK)was greater than 1.0. However, as the cation concentration was increased, PNH4/PK initially decreased to a minimum of 0.95 at 3 mM before increasing again to a maximum of 1.89 at 300 mM. At cation concentrations above 300 mM, PNH4/PK decreased slightly. This implies that the pore of the channel can be occupied by more than one cation simultaneously. Ammonium permeation through the pore was simulated using a model which is composed of three energy barriers and two energy wells (the ion-binding sites). The model (3B2S)allowed for single-file permeation, double cation occupancy, ion-ion repulsion within the pore and surface potential effects. Results indicated that energy peaks and energy wells were situated asymmetrically within the electrical distance of the pore, that cations repel each other within the pore and that the vestibules to the pore contain negligible surface charge. The energy profile obtained for NH+4 is compared with ones obtained for K+ and Na+. This information allows the fluxes through the K+ channel of the three major monovalent cations present in the soil solution to be predicted.
Keywords: AMMONIUM (NH+4); K+-CHANNEL; PERMEATION; PLANAR LIPID BILAYER; PLASMA MEMBRANE; RYE (SECALE CEREALE L.)